Spontaneous weight change during chronic hepatitis C treatment: Association with virologic response rates - Alwakeel, Hany R.; Zaghla, Hasan E.; Omar, Nabeel A.; Alashinnawy, Hasan A.; Rewisha, Eman A.; Matarese, Laura E.; Taha, Azza A.; Kandil, Hossam M. (My University, 2013)
We examined weight changes during chronic hepatitis C (CHC) therapy and association with virologic response. Weight changes were compared between subjects achieving rapid, early, and sustained virologic response rates (RVR, EVR, and SVR). RVR, EVR and SVR were compared among patients with or without weight loss of ≥ 0.5 body mass index (BMI) units (kg/m²) at 4, 12, 48 weeks. CHC therapy was initiated in 184 cases. Median pretreatment BMI was 27.7 (18.4-51.3) with 38% overweight and 31% obese (BMI ≥25 and ≥ 30, respectively). Among patients with liver biopsies (n = 90), steatosis was present in 31.6%; fibrosis grade of 1-2/6 in 46%, 3-4 in 37.3% and 5-6 in 14.7%. Mean weight loss at 4, 12, 24 and 48 weeks of therapy were 1.2, 2.6, 3.8 and 3.3 kg, respectively. After 4 and 12 weeks of treatment, 38% and 54.3% had a BMI decrement of ≥ 0.5 kg/m². For genotype 1, weight loss at 4 weeks was associated with significantly higher EVR (90.0% vs. 70%, p = 0.01) and a tendency towards better RVR and SVR (42.9% vs. 26.0% and 55.2% vs. 34.8%, respectively, p = 0.08). In multivariate analysis, weight loss at 4 weeks was independently associated with EVR (OR 6.3, p = 0.02) but was not significantly associated with RVR or SVR. Spontaneous weight loss at 4 and 12 weeks of CHC therapy was associated with improved EVR. Weight loss at 4 weeks was an independent predictor of EVR but not SVR.
Keywords: Weight change, hepatitis C, treatment outcomes, virologic response